MANTRA DAN IDENTITAS LINGUISTIK: PENDEKATAN FORENSIK DALAM PRAKTIK BUDAYA - Usman, Fajri; Delfia, Elly; Hadhiyansah, Hafizah; Fitri, Nidya (Universitas Hamzanwadi, 2026)
This study aims to examine Malay–Minangkabau mantras as ritual language practices through the perspectives of forensic linguistics and sociolinguistic–cultural studies. Specifically, the research seeks to identify the linguistic features of mantras at the phonological, morphological, syntactic, lexical, and pragmatic levels; to represent the linguistic identity of their speakers; and to explain the social and cultural functions of mantras within local communities. The study positions mantras not merely as magical texts or folklore, but as social–linguistic actions that record values, identity, and the cultural dynamics of the Malay–Minangkabau community. The scope of the research is limited to healing and protective mantras used in particular Malay–Minangkabau communities. The analysis focuses on linguistic structure and socio-cultural context without normatively evaluating medical or theological aspects. Employing a qualitative descriptive approach, this study integrates forensic linguistics, Halliday’s theory of social meaning (ideational, interpersonal, and textual), and the language–culture perspectives of Foley and Duranti. The research data consist of mantra texts obtained from the documentation of oral traditions and. The findings indicate that mantras exhibit formulaic and performative linguistic structures that function as mechanisms of psychosocial regulation within the community. A noteworthy finding is that mantras constitute a restricted ritual register with socially limited users and function as a collective linguistic fingerprint that records the identity, history, and cultural transformation of the Malay–Minangkabau community.